ALIH WAHANA NOVEL KE FILM CINTA LAKI-LAKI BIASA KARYA ASMA NADIA DAN GUNTUR SOEHARJANTO - Agus Nugroho (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2023)
This study aims to describe the process of ecranization of plot, characters, and background in the form of shrinking, adding and changing aspect categories varies on the novel and film Ordinary Male Love by Asma Nadia and Guntur Soeharjanto. The method used in this research is descriptive qualitative. The sources and data of this research are the novel and film Cinta-Laki Usually by Asma Nadia and Guntur Soeharjanto. Focus on this research in the form of the process of ecranization of the plot, characters and setting. Data obtained by technique reading, watching techniques, and note-taking techniques. There are 11 groove shrinkage, 22 groove additions, 8 varied changes to grooves. There are 3 shrinkage characters, 11 character additions, 2 varied changes to characters. And there are 2 backgrounds which were not shown, 10 sets were added to the film. Result of This study shows that the ecranization process that occurs in the groove elements, character and background, namely the existence of aspects of shrinking, adding aspects, aspects variable changes. Shrinking, adding, and changing varies This is done considering that novels and films are two different media. Film has limited time duration so it is likely that aspects of change will occur. But overall the depiction in the film not far from the depiction in the novel. Keywords: Novel, Film, Ecranization